2023
DOI: 10.1248/bpb.b22-00637
|View full text |Cite
|
Sign up to set email alerts
|

Brazilin Inhibits the Invasion and Metastasis of Breast Cancer

Abstract: This study aimed to determine the effect of brazilin on the invasion and metastasis of breast cancer. The breast cancer MDA-MB-231 and 4T1 cells were treated with brazilin to investigate proliferation and invasion using cell proliferation assay, wound healing assay, transwell assay. BALB/C mice were randomized into normal, model, positive control, and Sappan L. extract groups (n=6/group). The mice were injected with 4T1 cells via caudal veins to establish a lung metastasis model and via subcutaneous injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has been previously described that Brazilin inhibits NF-kB activation through interaction with its active site, inhibiting cell migration and invasion ( Haryanti et al, 2022 ). In a recent study, they also report that Brazilin inhibited the migration and invasion of MDA-MB-23 and 4T1 breast cancer cells; however, they do not describe the mechanism by which this occurs ( Yang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously described that Brazilin inhibits NF-kB activation through interaction with its active site, inhibiting cell migration and invasion ( Haryanti et al, 2022 ). In a recent study, they also report that Brazilin inhibited the migration and invasion of MDA-MB-23 and 4T1 breast cancer cells; however, they do not describe the mechanism by which this occurs ( Yang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lower the IC 50 value, the more cytotoxic the substance is ( Meyer et al, 2019 ). Based on its IC 50 value from different types of cancer cell lines ( Bello-Martínez et al, 2017 ; Handayani et al, 2017 ; Haryanti et al, 2022 ; Jenie et al, 2018 ; Suyatmi et al, 2022 ; Yang et al, 2023 ; Zhang et al, 2014 ), brazilin has a strong ability to treat breast cancer on 4T1 cell lines with the measured IC 50 value of 3.7 µM. The methods used in several studies to know the mechanism of brazilin to treat several types of cancer are shown in Table 1 .…”
Section: Brazilin Mechanisms In Cancermentioning
confidence: 99%
“…Brazilin can also be found in heartwood trees, including brazilwood ( Caesalpinia echinata ) and bralette ( Caesalpinia Violaceae ) ( Dapson and Bain, 2015 ). In several studies, we found that brazilin has the ability to treat several types of cancer, such as breast cancer ( Jenie et al, 2018 ; Hermawan and Putri, 2020 ; Jang et al, 2020 ; Chatterjee et al, 2022 ; Haryanti et al, 2022 ; Yang et al, 2023 ), colorectal cancer ( Handayani et al, 2017 ), multiple myeloma ( Kim et al, 2012 ), osteosarcoma ( Kang et al, 2018 ), lung cancer ( Suyatmi et al, 2022 ), cervical cancer ( Kitdamrongtham et al, 2013 ; Jeon et al, 2014 ), bladder carcinoma ( Zhang et al, 2015 ; Zhang et al, 2018 ), and others ( Lee et al, 2013 ; Mitani et al, 2013 ; Zhang et al, 2014 ; Bello-Martínez et al, 2017 ; He et al, 2017 ; Correia Soeiro et al, 2022 ; Yan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in both concentrations with brazilin there is a decrease of about 50% in cell migration (55 and 51 %, respectively). Recently, brazilin, isolated from Caesalpinia sappan, was described to inhibit cell migration, invasion, and metastasis in breast cancer [29]. On the other hand, it has been described that brazilin, n, , in combination with doxorubicin, has a cytotoxic and anti-migratory effect on MCF7 breast cancer cells [30].…”
Section: Cell Migrationmentioning
confidence: 99%
“…Active STAT form dimers and translocate to the nucleus when phosphorylated on tyrosine residues. The dimers bind to specific promoter sequences and modulate the transcription of genes that control cellular processes, such as proliferation, epithelial-mesenchymal transition (EMT), cell migration, differentiation, and apoptosis [29]. In uncontrolled processes due to inhibiting the transcription of genes that regulate this pathway, it is described that STAT3 is phosphorylated in 40% of breast cancer cases [30].…”
Section: Molecular Dockingmentioning
confidence: 99%